Uniaxial Compression Test and Numerical Study on the Mechanical Mechanism of Crack Exhibition and Propagation in Layered Rocks - Zhengnan Zhang; Xiangxin Liu; Bin Gong; Zhengzhao Liang; Xianxian Liu; Xun You (Applied Sciences, 2024)
Layered rocks are widely distributed in mining and underground engineering. The evolution processes, such as crack initiation, development and penetration, inevitably occur due to stress changes. This study carried out an experiment and numerical simulation to explore the correspondence between crack distribution and bedding dip, and to reveal the mechanical mechanism of layered rock fracturing. The results show that the layered rock specimens with different bedding dips obtained different stress combinations under the same uniaxial compression conditions. There are a total of five types of stress combinations, including pure compression type, compression shear type, pure shear type, tension shear type, and pure tension type. The Mohr circle is effective in characterizing the relationship between the stress combinations and failure modes. The failure mode of layered rocks in the range of 0° to 150° is presented the variation features of “tensile failure → compression-shear failure → shear failure → tensile shear failure → tensile failure”. Furthermore, the combined distributions of dominant and secondary cracks are summarized into the penetrating mode, the exfoliation mode, the feather crack mode, and the associated mode in high-dip of layered marbles. This paper provides research ideas for stability monitoring and crack tracking of layered rock mass engineering.